Reducing Junior High School Students’ Off-Task Behavior through Self-Monitoring and Reinforcement: A Single Subject Design Study - Anisa Safitri; Henny Indreswari; Khairul Bariyyah; Noradilah Md Nordin (International Journal of Applied Guidance and Counseling, 2026)
This study examined changes in off-task behavior among junior high school students through self-monitoring combined with reinforcement. Using a quantitative single-subject design with a multiple baseline across participants model, three students who frequently displayed off-task behavior during learning activities were selected through initial observation and teacher recommendation. The intervention involved identifying target behavior, recording focused and unfocused behavior, and providing verbal praise, positive feedback, and simple rewards when students reduced off-task behavior. Data were collected using an observation sheet and students’ self-monitoring sheets, then analyzed descriptively and visually across baseline, intervention, and follow-up phases. The results showed decreased off-task behavior across all subjects: Subject 1 from 9 to 3, Subject 2 from 10 to 4, and Subject 3 from 11 to 4. These findings indicate that self-monitoring with reinforcement can support the reduction of off-task behavior and increase students’ behavioral engagement during classroom learning.